2015
DOI: 10.3382/ps/peu051
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the protein secondary structure of hen's egg yolk determined by Fourier transform infrared spectroscopy during the first eight days of incubation

Abstract: In this study, incubation-induced alterations in the protein secondary structures of egg yolk and its major fractions (granules, plasma, and low-density lipoproteins [LDL]) were monitored during the first 8 d of embryogenesis using Fourier transform infrared spectroscopy (FTIR) and isoelectric focusing (IEF). Two factors potentially connected with egg yolk protein secondary structure changes were evaluated, i.e., the pH value of incubated egg yolk, and phosvitin, an important egg yolk protein assumed to play a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…The aforementioned results suggested that ovalbumin accumulated in egg yolk may be due to the transfer of ovalbumin from egg white into egg yolk to meet the needs of embryonic development (Moran, ). A recent study had demonstrated that egg white entered the egg yolk plasma at day 4 of incubation through Fourier transform infrared spectroscopy analysis (Lilienthal, Drotleff, & Ternes, ). It is generally accepted that an accumulation of fluid in the yolk cell occurs during the first 4–6 days of incubation results from the movement of albumen through the blastoderm (Babiker & Baggott, ; Latter & Baggott, ).…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned results suggested that ovalbumin accumulated in egg yolk may be due to the transfer of ovalbumin from egg white into egg yolk to meet the needs of embryonic development (Moran, ). A recent study had demonstrated that egg white entered the egg yolk plasma at day 4 of incubation through Fourier transform infrared spectroscopy analysis (Lilienthal, Drotleff, & Ternes, ). It is generally accepted that an accumulation of fluid in the yolk cell occurs during the first 4–6 days of incubation results from the movement of albumen through the blastoderm (Babiker & Baggott, ; Latter & Baggott, ).…”
Section: Resultsmentioning
confidence: 99%
“…The phosphorylation degree of ovalbumin increases during embryo development, which can not only enhance the absorption of minerals such as Ca 2+ and Mg 2+ but can also protect the embryo from oxidative damage. , Ovalbumin-like was involved in response to corticosterone, mineralocorticoid, and progesterone, which are related to a variety of physiological processes, including metabolism, inflammation, immunity, salt balance, and reproduction. , Therefore, the high abundance of ovalbumin-like before D18 might have significant physiological implications for early embryonic development. Previous studies have suggested that the abundance of ovalbumin in egg white was greatly reduced in the early embryonic development stage and then disappeared on D15 of incubation, and egg white entered the yolk plasma at D4 of incubation, and 10% of the egg white protein entered the yolk plasma after D10 of incubation. , In this study, the abundance of ovalbumin-like molecules decreased in the middle and late stages of incubation, probably because the rate of ovalbumin-like transfer from egg white to the yolk was less than the rate of uptake by embryos. Aminopeptidase and glutamyl aminopeptidase in egg white were responsible for the degradation of ovalbumin in fertilized eggs during incubation. , There were many degraded ovalbumin fragments in egg white during incubation .…”
Section: Resultsmentioning
confidence: 39%
“…Previous studies have suggested that the abundance of ovalbumin in egg white was greatly reduced in the early embryonic development stage and then disappeared on D15 of incubation, 41 and egg white entered the yolk plasma at D4 of incubation, and 10% of the egg white protein entered the yolk plasma after D10 of incubation. 42,43 In this study, the abundance of ovalbumin-like molecules decreased in the middle and late stages of incubation, probably because the rate of ovalbumin-like transfer from egg white to the yolk was less than the rate of uptake by embryos. Aminopeptidase and glutamyl aminopeptidase in egg white were responsible for the degradation of ovalbumin in fertilized eggs during incubation.…”
Section: -De-based Proteomic Analysismentioning
confidence: 49%
“…The peak in 1650–1600 cm −1 represented α‐helix structure (Long et al., 2015). It could be seen from Figure 6b that the absorption peak in the WP–Lac model changed from 1648.69 cm −1 (a w 0.33) to 1651.20 cm −1 (a w 0.54), indicating that the α‐helix content of WP gradually increased (Lilienthal et al., 2015). However, the absorption peak in CN–Lac model changed from 1656.52 cm −1 (a w 0.33) to 1655.70 cm −1 (a w 0.54), indicating that the a‐helix content of casein decreased.…”
Section: Resultsmentioning
confidence: 99%